1987
DOI: 10.1104/pp.85.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Trifolitoxin Production and Nodulation Are Necessary for the Expression of Superior Nodulation Competitiveness by Rhizobium leguminosarum bv. trifolii Strain T24 on Clover

Abstract: Many reports document the ability of certain Rhizobium strains to occupy nodules to the exclusion of other strains. The molecular basis of the superior nodulation competitiveness of any strain is not known, although important advances in recent years have been made (7-9, 12, 19, 20 (12,15,16,22,23,25,26).Hodgson et al. (12) have suggested that bacteriocin production by R. leguminosarum bv. trifolii CB782 is involved in its superior nodulation competitiveness. This was shown by co-inoculating CB782 with bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 18 publications
2
77
0
Order By: Relevance
“…Three were found that could no longer produce TFX on minimal medium (BSM-N), i.e., Tn5-1, Tn5-2, and Tn5-3 (34). Tn5-4 is a Tn5 derivative of T24 which is unaffected in TFX production (34). When plasmids harboring the tfxABCDEFG fragment were conjugated into each of the T24::Tn5 derivatives, we noticed that the zone of inhibition produced by the Tn5-2 derivative was smaller than those produced by the Tn5-1 and Tn5-3 derivatives (data not shown).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Three were found that could no longer produce TFX on minimal medium (BSM-N), i.e., Tn5-1, Tn5-2, and Tn5-3 (34). Tn5-4 is a Tn5 derivative of T24 which is unaffected in TFX production (34). When plasmids harboring the tfxABCDEFG fragment were conjugated into each of the T24::Tn5 derivatives, we noticed that the zone of inhibition produced by the Tn5-2 derivative was smaller than those produced by the Tn5-1 and Tn5-3 derivatives (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…In initial studies of the genetics of TFX production, R. leguminosarum bv. trifolii strain T24 was mutagenized with the transposon Tn5 (34). Approximately 5,600 Tn5 mutants were screened.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such studies have shown that competitiveness is affected by motility and chemotaxis (Ames & Bergman, 1981 ;Caetano-AnollCs et al, 1988;Liu et al, 1989;Mellor et al, 1987;Zdor & Pueppke, 1991), cell surface polysaccharides (Araujo & Handelsman, 1990;Bhagwat & Keister, 1990;Handelsman et al, 1984;Milner et al, 1992;Trinick & Hadobas, 1989;Ugalde et al, 1986;Zdor & Pueppke, 1991;Lagares et al, 1992), bacteriocin production (Triplett & Barta, 1987), succinate-sensitivity (Urban, 1988), and rate of nodule induction (Hahn & Hennecke, 1988). Such studies have also demonstrated that the ability to fix nitrogen (Amarger, 1981;Hahn & Struder, 1986;Sanjuan & Olivares, 1991 b) and to metabolize particular aromatic compounds (Rynne et al, 1988) does not affect competitiveness under the conditions tested.…”
Section: Introductionmentioning
confidence: 99%